2015
DOI: 10.1038/xyza.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Chaperone-like protein p32 regulates ULK1 stability and autophagy

Abstract: Mitophagy mediates clearance of dysfunctional mitochondria, and represents one type of mitochondrial quality control, which is essential for optimal mitochondrial bioenergetics. p32, a chaperone-like protein, is crucial for maintaining mitochondrial membrane potential and oxidative phosphorylation. However, the relationship between p32 and mitochondrial homeostasis has not been addressed. Here, we identified p32 as a key regulator of ULK1 stability by forming complex with ULK1. p32 depletion potentiated K48-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 26 publications
0
29
0
Order By: Relevance
“…Based on several previous reports, [14][15][16] the ULK1 protein could be degraded either as a part of the autophagosomal membrane or in proteasomes. Therefore, we tested the effect of lysosomal and proteasomal degradation inhibitors bafilomycin A 1 and MG132 on stabilization of the ULK1 protein.…”
Section: Ulk1 Protein Levels Are Rapidly Reduced During Cell Starvationmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on several previous reports, [14][15][16] the ULK1 protein could be degraded either as a part of the autophagosomal membrane or in proteasomes. Therefore, we tested the effect of lysosomal and proteasomal degradation inhibitors bafilomycin A 1 and MG132 on stabilization of the ULK1 protein.…”
Section: Ulk1 Protein Levels Are Rapidly Reduced During Cell Starvationmentioning
confidence: 99%
“…13 Some other proteins, including HSP90 and CDC37 and the recently identified chaperone-like protein C1QBP/p32, also regulate ULK1 stability and autophagy. 14,15 It has also been reported that binding of Atg8 to Atg1/ULK1 in an Atg8-intearcting motif/LC3-interacting region delivers Atg1/ULK1 within an autophagosome for lysosomal degradation in yeast and mammals, 16 suggesting a negative feedback loop in autophagy regulation.…”
Section: Introductionmentioning
confidence: 99%
“…Further evidence that AMPK activation may indeed lead to an upregulation of p32 activity is demonstrated by the direct phosphorylation of p32 by ATM (Ataxia-telangiectasia mutated, an upstream activator of AMPK) and p32's association with TFAM, a mitochondrial transcription factor necessary for mitochondrial DNA transcription and biogenesis whose expression is increased by AMPK activation [51,165]. Particularly compelling is the recent finding that p32 is essential in the regulation of autophagy by forming a complex with and stabilizing the activity of ULK1, a serine-threonine kinase that is necessary for autophagic induction [166]. Indeed, p32 silencing significantly impaired both starvation-and rapamycin-induced autophagic flux [166].…”
Section: Ampk Activation and Mitochondrial Atp Production Is Essentiamentioning
confidence: 94%
“…Particularly compelling is the recent finding that p32 is essential in the regulation of autophagy by forming a complex with and stabilizing the activity of ULK1, a serine-threonine kinase that is necessary for autophagic induction [166]. Indeed, p32 silencing significantly impaired both starvation-and rapamycin-induced autophagic flux [166]. Because AMPK has also been shown to regulate autophagy by phosphorylating and activating ULK1 and both rapamycin (mTOR inhibitor) and sulforaphane (isothiocyanate found in cruciferous vegetables) have each been shown to enhance autophagic clearance of progerin, a novel AMPK-p32 axis is further implicated, potentially decreasing progerin production via alternative splicing modulation while enhancing progerin clearance through autophagic induction [32,167,168].…”
Section: Ampk Activation and Mitochondrial Atp Production Is Essentiamentioning
confidence: 97%
See 1 more Smart Citation